DESAIN PENGENDALIAN INTERNAL UNTUK MENINGKATKAN KUALITAS UDANG WINDU PADA BADAN USAHA “X” DI BANYUWANGI - Azizah Dione; Yenny Sugiarti (Perpustakaan Universitas Surabaya, 2018)
In running a company, every activity that occurs requires the right internal controls to achieve corporate objectives. The weak quality of shrimp produced by the company shows the weakness of the company's internal control. COSO-based internal controls should be applied to shrimp farming activities in order to obtain quality in accordance with company standards. This research uses the object of research of shrimp aquaculture business in Banyuwangi and using model theory of COSO Framework. In the evaluation of the researchers, it was found that the company has poor quality of shrimp due to its weak internal control system in the control environment and control activities, which is no organizational structure, job description, standard operating procedure, work instructions, and documents for shrimp farming activities. Researchers provide recommendations for leaders by making the design of organizational structure, job description, standard operating procedures, work instructions, and document improvements to make the company achieve its goals.